Insects in bioregenerative life support systems: unlocking their role in space sustainability - Berggren, Åsa; Jensen, Annette Bruun; Copplestone, David; Guidetti, Roberto; Heer, Martina; Pittia, Paola (Frontiers in Physiology, 2025)
Long-duration space missions and planetary colonization efforts will depend on Bioregenerative Life Support Systems (BLSS) for sustainable food production, water recycling, and waste management. However, most BLSS research to date has focused almost exclusively on plants, with limited attention to animals and species-level ecological interactions. Here, we review 280 BLSS-focused studies and identify significant underrepresentation of insects and invertebrates, despite their multifunctional potential for nutrient recycling, protein production, and ecological resilience. Only 13 studies experimentally included insects, and these are rarely explored in interactions with other species in the system. Insects such as Acheta domesticus, Tenebrio molitor and Bombyx mori show promise but remain underexamined under space-relevant conditions. Comparisons with terrestrial circular food systems reveal parallel knowledge gaps but also highlight emerging evidence supporting invertebrates as integral components. We argue that closing these gaps will require targeted research on insect physiology and species interactions under space-like stressors such as microgravity and radiation. Drawing on insights from Earth-based circular food systems can accelerate the integration of multifunctional insect species into closed-loop space habitats. Addressing these gaps is essential to create robust, resilient bioregenerative systems that can support human life beyond Earth.